Performance Insights Into Supporting Kokkos Views in the Kokkos Comm MPI Library - Avans, C. Nicole; Ciesko, Jan; Pearson, Carl; Suggs, Evan Drake; Olivier, Stephen L.; Skjellum, Anthony (2024 IEEE International Conference on Cluster Computing Workshops (CLUSTER Workshops), 2024)
In this poster, we introduce Kokkos Comm, a new Kokkos ecosystem library designed to address the challenges of integrating Kokkos, a C++ performance portability ecosystem, with distributed memory programming models. Kokkos Comm aims to alleviate the difficulties associated with coordinating non-blocking MPI operations and Kokkos execution spaces, as well as handling non-contiguous data structures represented by Kokkos Views. Additionally, it serves as a platform for researching im-proved methods of managing non-contiguous data and exploring new communication APIs across various underlying transports.